“From private conversations to political projects” Political friendship among elite catholic women. First half of the 20th century - Bravo Olmedo, Valentina; Lillo, Patricia (Revista de Historia Social y de las Mentalidades, 2026)
During the first decades of the twentieth century, elite Catholic women in Chile developed important social and educational organizations that transformed the landscape of female Catholic activism. Although these institutions have been studied from administrative and sociocultural perspectives, the conceptualization and analysis of political friendship as a driver of social change remain largely unexplored. This article proposes to define female political friendship as the convergence of complicities among women who, by sharing a common space of class, gender, and historical experience, mobilize their individual ideas and feelings toward collective work with public impact. Through the analysis of personal documents, Catholic press, and institutional records of the Liga de Damas (1912) and the Hogar Catequístico (1936), we study the networks of sociability and affective bonds between their founders, Amalia Errázuriz de Subercaseaux and Elisa Valdés Ossa. This research contributes to theorizing political friendship as a category of historical analysis, revealing its fundamental role in shaping Chilean female Catholic activism and opening new perspectives for understanding forms of agency in the history of Catholic women.